FRAUD DETECTION OF FINANCIAL STATEMENTS WITH DIAMOND FRAUD ANALYSIS - Deliana Deliana; Ruth Rebecca Oktalia (Universitas Pendidikan Indonesia, 2022)
This study aims to empirically test the detection of financial statement fraud using Fraud Diamond analysis which explains the factors that influence the occurrence of fraud. The population in this study is the infrastructure, utility, and transportation sector companies listed on the Indonesia Stock Exchange in 2016 – 2019 with a total of 83 companies. A total of 12 companies were sampled using the purposive sampling technique. This study uses secondary data and the analytical method used is multiple linear regression analysis with SPSS tools. The results of this study indicate that the level of Leverage (LEV) affects financial statement fraud. Changes in total assets (ACHANGE), Return On Assets (ROA), Insider share ownership (OSHIP), Special party transactions (RPT), Independent audit members (BDOUT), Change of Public Accounting Firm (KAP) (AUDCHANGE), and Changes in the Board of Directors (DCHANGE) does not affect financial statement fraud.